2012
DOI: 10.1080/02640414.2011.652654
|View full text |Cite
|
Sign up to set email alerts
|

Biological maturation, morphology, fitness, and motor coordination as part of a selection strategy in the search for international youth soccer players (age 15–16 years)

Abstract: We report the morphology (height, weight, body fat, body mass index), fitness (strength, speed, agility, flexibility), and soccer-specific (dribbling) and non-specific motor coordination skills (Körper KoordinationsTest für Kinder; KTK) of 78 Belgian international youth soccer players aged 15-16 years with varying biological maturity status. The more mature players (U16 and U17) possessed higher morphological measures and outperformed their later maturing peers (U16 Futures and U17 Futures) on almost all fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(162 citation statements)
references
References 24 publications
6
141
2
13
Order By: Relevance
“…However, previous studies in the area have produced contradictory results as to whether motor coordination can be improved as an outcome of intensive sport-related practice [6,[10][11][12]20]. The results of this study provide evidence highlighting that motor coordination skills assessed across adolescence demonstrate greater variability than previously reported [5,6].…”
Section: Discussionmentioning
confidence: 50%
“…However, previous studies in the area have produced contradictory results as to whether motor coordination can be improved as an outcome of intensive sport-related practice [6,[10][11][12]20]. The results of this study provide evidence highlighting that motor coordination skills assessed across adolescence demonstrate greater variability than previously reported [5,6].…”
Section: Discussionmentioning
confidence: 50%
“…Biological maturation is sometimes considered a confounding factor in motor performance, given that increments in speed, endurance and power have been observed around the time of age at peak height velocity (Philippaerts et al, 2006). Vandendriessche et al (2012) studied how biological maturation may affect fitness and motor coordination skills, but in a specific sample -male soccer players aged 15-16 years. These authors reported that more mature players outperformed their later maturing peers on almost all fitness tests, but motor coordination tests assessed by KTK battery did not differentiate the more mature group from their latter peers.…”
Section: Discussionmentioning
confidence: 99%
“…Da costa et al [15] investigated the frequency, efficiency, and performance index of soccer players in training, comparing them by game category, while the majority of studies have focused on high performance athletes [14,16]. It is known that regional players tend to underestimate the performance results of national players [17]; however, this should be investigated through tactical aspects, relevant to understand whether different principles are executed with similar efficiency between regional players.…”
Section: Introductionmentioning
confidence: 99%